Health of students and the role of physical education in its provision. - Futornyі S.М. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2011)
The paper analyzes the data of modern scientific literature on the formation of health and the foundations of physical fitness in the process of physical education students. A college education - is an important stage in the formation of a future specialist of the new formation. Big role in an integrated system of educational process belongs to physical education. Physical education is one of the most important factors in forming, maintaining and strengthening the health of students. Its aim - to promote harmonious development of training highly qualified specialists. In recent years, there is a need for drastic restructuring process of physical education in schools, introduction of innovative approaches and technologies on the organization of sports and recreation activities in the education of students. One priority of physical education is to develop students' knowledge and skills of physical fitness, meaningful relationship to the preservation of his health. However, at present the number of effective information and learning systems designed to lay the groundwork for a physical fitness, and their use in the physical education of students is very sparse and requires further in-depth scientific development.